Tl4GdTe3 and Tl4DyTe3 – novel structural Tl5Te3 analogues - Imamaliyeva, S. (Physics and Chemistry of Solid State, 2020)
The novel ternary compounds Tl4GdTe3 and Tl4DyTe3 - structural analogs of Tl5Te3 (Sp.gr.I4/mcm), were synthesized and identified by DTA and XRD methods. From powder XRD data, their crystal lattices parameters were calculated: a=8.8766(7), c=13.0846 (13) Å, Z=4 (Tl4GdTe3); a=8.8588 (9), c=13.0524(16) Å, Z=4 (Tl4DyTe3). It was found that the synthesized compounds melt with decomposition by peritectic reactions at 770 and 762 K, respectively.